International Financial Reporting Standards Convergence Process for Small and Medium-Sized Entities - Gök, Görkem (International Journal of Engineering and Management Sciences, 2024)
The "International Financial Reporting Standards (IFRS) Convergence Process for Small and Medium-Sized Entities (SMEs)" seeks to address the unique challenges and requirements faced by smaller businesses in adhering to international accounting and reporting standards. This initiative recognizes that SMEs operate in diverse economic environments and have distinct financial reporting needs compared to larger enterprises. The primary purpose of this convergence process is to enhance the relevance, accessibility, and practicality of IFRS for SMEs, fostering consistency in financial reporting practices across global markets.A project to create accounting standards appropriate for small and medium-sized businesses (SMEs) is being worked on by the International Accounting Standards Board. This abstract provides an overview of the convergence process involving International Financial Reporting Standards (IFRS) for Small and Medium Sized Entities (SMEs). With the global landscape of financial reporting constantly evolving, the integration of IFRS tailored specifically for SMEs marks a pivotal transition towards harmonizing financial reporting practices. This paper examines the essential elements and implications of this convergence, addressing the challenges and benefits faced by SMEs as they align with these international standards. The analysis delves into the driving factors behind the convergence, including the necessity for a unified and transparent financial reporting framework, aiming to facilitate comparability and accessibility of financial information across borders. Furthermore, the abstract discusses the potential impact on SMEs’ financial reporting quality, decision-making processes, and access to capital. Through a comprehensive review of the convergence process, this abstract seeks to contribute to the understanding of the significance and implications of adopting IFRS for SMEs, thereby providing valuable insights for practitioners, regulators, and stakeholders in the financial reporting ecosystem.